Use of ultrasound combined with magnetic resonance imaging for diagnosis of breast masses and fibroids - Wei Xiang; Zihui Huang; Chenhu Tang; Bo Shen; Qun Yu; Xiaohong Niu; Fanrong Meng (Journal of International Medical Research, 2019)
Objective To investigate the clinical value of ultrasound plus magnetic resonance imaging (MRI) for the diagnosis of breast masses and fibroids. Methods Clinical data for 357 patients with breast masses diagnosed at our hospital were analyzed retrospectively. The diagnostic performances were compared between 243 patients who underwent routine ultrasound examinations (control group) and 114 patients who underwent routine ultrasound plus MRI (test group). Results The overall accordance rates of routine ultrasound and routine ultrasound plus MRI for the diagnosis of breast masses, based on postoperative pathological diagnoses, were 70.78% (172/243) and 90.35% (103/114). The addition of MRI significantly improved the overall diagnostic performance of routine ultrasound for breast masses. The diagnostic accordance rate of routine ultrasound for the diagnosis of breast fibroids (fibroadenomas) was 74.12% (63/85 cases) compared with 93.94% (31/33 cases) for routine ultrasound plus MRI. The diagnostic performance of routine ultrasound plus MRI was therefore also significantly higher than routine ultrasound alone for diagnosing breast fibroids. Conclusions Routine ultrasound plus MRI can greatly improve the diagnostic accordance rates for breast masses and fibroadenomas.